Biochemical Predictors of Elevated Blood Pressure and Cardiometabolic Risk in School-Aged Children: A Cross-Sectional Study - Anwar, Sidra; Munir, Khurram; Saeed, Saboohi; Rahim Memon, Farzana; Ejaz, Maryam; Hussain , Asma (Journal of Neonatal Surgery, 2025)
Background: Hypertension is emerging in children, mainly due to obesity and lifestyle changes. Early biochemical markers may help detect cardiometabolic risk before clinical disease appears. Objective: To determine the association between selected biochemical markers and elevated blood pressure in school-aged children. Methods: A cross-sectional study was conducted among 220 children aged 8–14 years from three schools. Blood pressure was categorized according to age- and height-specific percentiles. Fasting blood samples were analyzed for lipid profile, fasting glucose, fasting insulin, HOMA-IR, uric acid, high-sensitivity CRP (hs-CRP), and vitamin D levels. Anthropometry and BMI percentiles were recorded. Results: Pre hypertension and hypertension were found in 14.5% and 6.8% of children, respectively. Mean systolic BP was higher in children with high LDL (112.7 ± 8.5 mmHg) compared to normal LDL (105.4 ± 7.9 mmHg, p < 0.01). Insulin resistance (HOMA-IR > 2.5) was present in 28% of participants. Children with elevated HOMA-IR had significantly higher systolic BP (113.6 ± 9.1 mmHg) compared to those without insulin resistance (104.9 ± 7.5 mmHg, p < 0.001). Uric acid showed a moderate positive correlation with systolic BP (r = 0.42). Elevated hs-CRP (>3 mg/L) was detected in 18% of participants and was associated with higher BMI and BP. Vitamin D deficiency (<20 ng/mL) was common (62%) but showed a weak association with BP. Conclusion: LDL cholesterol, insulin resistance, uric acid, and hs-CRP are strong biochemical predictors of elevated blood pressure in children. Routine screening in overweight and obese children may help identify early cardiometabolic risk